Two-stage efficiency evaluation of industrial water resources and the role of digital inclusive finance: insight from Yangtze River Delta - Linjie Feng; Tingting Liu; Zhenjie Yang; Yi Shi; Hongxi Chen; Ka Leong Chan; Bin Chen (Applied Water Science)
Abstract The Yangtze River Delta (YRD) occupies 2.1% of China's territory but accounts for 1/4 of its GDP. Boosting efficiency of industrial water resources in YRD will drastically decrease water pollution and resource constraints. The current paper employed Network Super-SBM and the Global Malmquist-Luenberger index to evaluate industrial water use efficiency and wastewater treatment efficiency of YRD’ cities. Furthermore, digital inclusive finance and green innovation are introduced to investigate the mechanisms underlying their influence on the overall industrial water resources efficiency. The empirical findings posts that: (1) there is still room to improve the overall efficiency, especially the water treatment efficiency; (2) the MI value of each stages in most samples is greater than 1, indicating that the water treatment efficiency and water use efficiency are improving. It is mainly driven by the improvement of the efficiency of the management; (3) there are substantial differences in water resource efficiency among metropolitan areas, with Nanjing-metropolitan areas and Hefei-metropolitan areas having higher water use efficiency and water treatment efficiency for both stages, while Hangzhou-metropolitan areas and Shanghai-metropolitan areas have lower water treatment efficiency. As shown by the Kernel density Estimation, the degree of efficiency dispersion within same metropolitan area is reducing; and (4) digital inclusive finance will boost overall efficiency and water treatment efficiency, with green innovation as a mediating factor. The findings herein offer compelling evidence that financial development increases the effectiveness of water resources, introduce fresh perspectives for the government to put forward water-related policies, and provide ideas for high-quality economy.